Maria Ivanova, Bogdan Athanassov, Vanya Petrova, Desislava Takorova and Philip W. Stockhammer (eds). Social Dimensions of Food in the Prehistoric Balkans. - Souvatzi, Stella (Journal of Greek Archaeology, 2019)
Food practices and their social implications are an important focus of investigation for a wide range of disciplines. In anthropology in particular the cross-cultural importance of meals or of the exchange of food and substances in creating and enduring social bonds gained attention already in Malinowski’s era and has remained a central theme of inquiry ever since. It is now widely acknowledged that food practices play an active role in the negotiation of social identities, relationships and distinctions at different social scales. In archaeology, the economic dimensions of subsistence practices have always held an interest, but food itself was not recognised as a significant analytical or theoretical concept until recently. Since the 2000s, however, there is a growing interest in the cultural and social analysis of food, accompanied by a surge of novel perspectives and methods in palaeo-botanical, zoo-archaeological, palaeo-anthropological and material culture research, including the regions in question here.